Modele edytorskie XIX-wiecznych polskojęzycznych wydań Nowego Testamentu – próba identyfikacji - Zakonnik, Łukasz (The Biblical Annals, 2022)
The presented article reviews publications of 19th century Polish New Testament in order to find editorial models upon which subsequent editions were based. The work considers 68 editions published between 1815–1900. The first half of them were based on the translation adopted in the Danzig Bible and the second half on the translation by Jakub Wujek. Among the analyzed editions, 27 were identified, according to which subsequent Polish New Testament were published (in the 19th century). In addition to the editorial models indicated, the work also proposes 7 editing lines.